A values approach to understanding ethical business relationships in the 21st century: A comparison between Germany, India, the People's Republic of China, and the United States - Fraedrich, John (Teaching business ethics, 2000)
The purpose of this study was to examine howmanagerial values may differ between future managersfrom Germany, India, the People's Republic of China(PRC), and the United States (U.S.) and to considerhow these differences may influence current and futureethical business relationships. The results show thatthere are significant differences between countries onthe acceptance of authority with the exception of theU.S. and the PRC. All countries sampled were high onneed determined expression with nonsignificancebetween the means of the PRC/U.S. and Germany/U.S. Allcountries sampled were significantly high onequalitarianism and individualism was high for allcountries except the PRC and India, which were notsignificant. The results point to the increasedcommonality between future managers across the fourcountries as opposed to the traditional stereotypesassociated with each culture. Possible implicationsare discussed relative to the 21st century andorganizations that are involved in interculturalhiring.